Penempatan Tenaga Kerja Program Antar Kerja Antar Daerah - Medan Yonathan Mael (Jurnal Poros Politik, 2019)
The quality and capability of the Indonesian workforce as a whole is still relatively low as reflected in the low level of work productivity, both in terms of level and growth. The purpose of this study is to describe and analyze the placement of Inter-Regional Workers (AKAD) in TTU Regency. The method used in this research is descriptive qualitative with a focus of research on the level of understanding of labor laws, the intensity of the socialization of labor laws, the level of coordination between the Government and related partners such as NGOs, PJTKI and related agencies. Level of Accuracy in Placement of labor mechanism AKAD service and budget amount. The data analysis technique used in this study is the interactive model of Milles and Hubermans. The results showed that job seekers did not know the Law No.39 of 2004 about labor. Department of Manpower and Transmigration not intesified to socialize. Coordination has not been substantial and integrated. The absence of a budget related to AKAD is not in the budget of the Office of Manpower and Transmigration. Then the need for socialization of labor laws to the public and prospective workers by the Office of Manpower and Transmigration.